Pharmacological FGF21 signals to glutamatergic neurons to enhance leptin action and lower body weight during obesity - Kristin E. Claflin; Andrew I. Sullivan; Meghan C. Naber; Kyle H. Flippo; Donald A. Morgan; Tate J. Neff; Sharon O. Jensen-Cody; Zhiyong Zhu; Leonid V. Zingman; Kamal Rahmouni; Matthew J. Potthoff (Molecular Metabolism, 2022)
Objective: Fibroblast growth factor 21 (FGF21) is a peripherally-derived endocrine hormone that acts on the central nervous system (CNS) to regulate whole body energy homeostasis. Pharmacological administration of FGF21 promotes weight loss in obese animal models and human subjects with obesity. However, the central targets mediating these effects are incompletely defined. Methods: To explore the mechanism for FGF21's effects to lower body weight, we pharmacologically administer FGF21 to genetic animal models lacking the obligate FGF21 co-receptor, β-klotho (KLB), in either glutamatergic (Vglut2-Cre) or GABAergic (Vgat-Cre) neurons. In addition, we abolish FGF21 signaling to leptin receptor (LepR-Cre) positive cells. Finally, we examine the synergistic effects of FGF21 and leptin to lower body weight and explore the importance of physiological leptin levels in FGF21-mediated regulation of body weight. Results: Here we show that FGF21 signaling to glutamatergic neurons is required for FGF21 to modulate energy expenditure and promote weight loss. In addition, we demonstrate that FGF21 signals to leptin receptor-expressing cells to regulate body weight, and that central leptin signaling is required for FGF21 to fully stimulate body weight loss during obesity. Interestingly, co-administration of FGF21 and leptin synergistically leads to robust weight loss. Conclusions: These data reveal an important endocrine crosstalk between liver- and adipose-derived signals which integrate in the CNS to modulate energy homeostasis and body weight regulation.